If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8.5x + -5y + 12 + -3.5x = 0 Reorder the terms: 12 + -8.5x + -3.5x + -5y = 0 Combine like terms: -8.5x + -3.5x = -12x 12 + -12x + -5y = 0 Solving 12 + -12x + -5y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12x + -12 + -5y = 0 + -12 Reorder the terms: 12 + -12 + -12x + -5y = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -12x + -5y = 0 + -12 -12x + -5y = 0 + -12 Combine like terms: 0 + -12 = -12 -12x + -5y = -12 Add '5y' to each side of the equation. -12x + -5y + 5y = -12 + 5y Combine like terms: -5y + 5y = 0 -12x + 0 = -12 + 5y -12x = -12 + 5y Divide each side by '-12'. x = 1 + -0.4166666667y Simplifying x = 1 + -0.4166666667y
| x^4+12x^3-45x^2=0 | | 3m+7.5= | | 0=-4t^2+24t | | x^4+7x^3-30x^2=0 | | x^2-10x+23=0 | | 19=(-2x)+4 | | 9-3p=8 | | 2x^2+50x+9=5 | | 4x^2-15x-97=0 | | 0.5x+19.3=x-5.55 | | 2x^2+693=4x | | 0.9x+2.64=-0.5x+0.64 | | x^3+5x^2-10x=0 | | 600x-0.32=400x+0.94 | | 9.7=8x+2.5 | | (4x-1)(x)=18 | | y-2.2=10 | | 4x-26.7=x | | 7(x-1.8)=7.7 | | 8.2y+6.99=-64.35 | | 3x+16=2x+10 | | 72x^4+132x^3-36x^2-24x=0 | | x+3.1=6.4 | | 15=z-14 | | (11x+z)(11x-z)=0 | | m-31=-7 | | 3(x+1)=8(x-2)-16 | | (5a+6)(9a^2-8a-4)=0 | | 400x-0.21=600x+0.89 | | 3x+3(5x-7x)=12x-x | | 9x-2=7x-8 | | (3x+7)(2x-1)=0 |